Effect of VRM on a polymetallic sulfide ore and the flotation response as compared to conventional wet and dry rod milling - Nyakunuhwa, Hebert Simbarashe (Department of Chemical Engineering, 2020)
Comminution is an energy intensive, size reduction and mineral dressing process which consumes up to 50% of concentrator energy consumption. Conventional methods use mainly a combination of crushers and tumbling mills in comminution circuits. Energy consumption in these circuits has been found to be relatively high. To reduce the energy requirements, compression grinding equipment, Vertical Roller Mills (VRMs) and High-Pressure Grinding Rolls (HPGRs) have been identified as potential solutions, and they have been adopted in the cement industry. Reports from plants where these technologies have been installed in circuits indicate they are more energy efficient than the conventional comminution circuits. Studies have also suggested that the use of VRMs results in comminution products with relatively higher mineral liberation degrees. Unlike in the cement industry, comminution equipment in mineral processing circuits are also required to produce particles that can be separated and recovered in downstream processes. Froth flotation is a selective separation process that utilises differences in surface properties to separate value minerals from unwanted gangue. The success of flotation is dependent on chemistry, operational and equipment factors. The chemistry factors consider the interaction between flotation reagents and solids particles surface. The operational factors consider the effect of particle size distribution, mineralogy, feed rate, pulp density, pulp potential (Eh), bubble size, temperature and circuit design on flotation. The use of different comminution procedures may result in flotation feeds of different particle size distributions (PSDs), mineral liberation characteristics and pulp potential. Due to these differences, the resultant flotation response may differ. The present study was aimed at assessing the particle size distribution, mineral liberation profiles and the flotation response from material comminuted using the VRM floated under batch flotation conditions in a 3 litre Barker flotation cell. A complex polymetallic sulfide ore containing chalcopyrite (1.3 %), galena (2.4 %) and sphalerite (1.8 %) as the main value minerals and magnetite (68.0 %) and quartz (15.7 %) as dominant gangue minerals was used for the study. The ore was milled to target grinds of 55 %, 60 %, 65 %, 70 % and 75 % passing 75 µm respectively, at a grinding pressure of 600 kPa, air temperature of 300 K. For the benchmarking grind of 65 % passing 75 µm, the ore was also milled using heated air of temperature of 373 K and at elevated grinding pressures of 800 kPa and 1000 kPa. Further work was performed to evaluate if the VRM results are comparable to conventional dry and wet rod milling products floated under the same batch flotation conditions. An increase in grinding pressure was observed to result in an increase in throughput and a general decrease in specific energy consumption without a change in product particle size distribution nor the recovery of chalcopyrite, galena and sphalerite. Using heated air (373 K) resulted in the production of slightly less fines in the comminution products. The recovery of chalcopyrite, galena and sphalerite were not affected by the change in operating temperature. However, concentrate grade (selectivity) was compromised at elevated temperatures of comminution probably due to surface oxidation. The results indicated that the grind range to achieve the best flotation performance when using the VRM as a comminution device is between 60 % and 70 % passing 75 µm. The results also indicated that at the benchmarking grind of 65 % passing 75 µm, the specific energy consumption for comminution using the VRM was 54.3 % lower than that of the conventional tumbling mill circuit. The grind of 55 % passing 75 µm resulted in lower flotation efficiencies as the minerals were unlikely liberated enough whereas the grind of 75 % passing 75 µm resulted in poor performances due to low water recovery. Comparing VRM with wet and rod milling, the different comminution procedures resulted in flotation feed of similar PSDs for all grinds compared. The wet and dry rod milling products of grinds 55 % and 75 % passing 75 µm achieved better recoveries of chalcopyrite, galena and sphalerite as compared to the VRM performance mainly due to high water recoveries achieved. While mineral recoveries were above 90 % for the grinds of 60 % and 70 % passing 75 µm, the rod milling products had statistically better flotation recoveries at 95 % confidence compared to the VRM products. The mineral recoveries after dry rod milling were marginally better than after wet rod milling due to the minimisation of galvanic interactions during dry rod milling. For the benchmarking grind of 65 % passing 75 µm, VRM grinding resulted in 84 %, 84 % and 90 % liberated chalcopyrite, galena and sphalerite respectively. The liberation of chalcopyrite, galena and sphalerite after wet and dry rod milling were 80 %, 78 % and 90 % respectively. Chalcopyrite recovery was 96.7 %, 96.3 % and 96.7 % for the VRM, dry rod mill (RD) and wet rod mill (RW) products respectively. Galena recovery was 94.3 %, 94.3 % and 92.9 % for the VRM, RD and RW products respectively. Sphalerite recovery was 96.6 %, 97.4 % and 97.4 % for the VRM, RD and RW products respectively. The differences in recovery were statistically insignificant at 95 % confidence. Liberation differences did not translate to differences in recoveries as the ore was coarse grained. The recovery kinetics were very fast and independent of comminution procedure. Reference to the benchmarking grind therefore, the VRM can be retrofitted into existing plant installations as it is more energy efficient and the flotation performance was similar when using the flotation procedure tailored for tumbling mill-flotation systems.